Christian Nationalism, Civic Republicanism, and Radical Secularism in Contemporary American Politics over Time - Smidt, Corwin E. (Religions, 2024)
Over the past decade, a burgeoning strand of scholarly and journalistic literature has emerged that emphasizes the role of Christian nationalism within contemporary American politics. Unfortunately, this scholarly literature has mushroomed so quickly that relatively little attention has been given to its conceptual underpinnings and how Christian nationalism may be related to, or different from, other conceptualizations of the role of religion in public life. This article outlines different conceptualizations of Christian nationalism that have been advanced, analyzes how different coding schemes of its present measurement yields different assessments of its presence within American politics, and differentiates between and among different types of approaches to the role of religion in American public life. Using data drawn from Baylor national surveys on religion conducted in 2007, 2017, and 2021, this article examines three distinct groups within American politics—namely, Christian nationalists, civic republicans, and radical secularists—and how the relative size and characteristics of such groups have changed within American society over time.